Energy and angular distributions of electrons from sodium atoms photo-ionized with femtosecond laser pulses. (5th August 2021) - Boran, Y; Hart, N; Kaya, N; Zhou, J; Kolomenskii, A A; Schuessler, H A
Abstract: We studied photoelectron angular distributions (PADs) and energy spectra of sodium atoms photo-ionized with intense short laser pulses in the near-infrared region. Energy spectra of photoelectrons due to multistep ionization of sodium atoms through intermediate levels 5 p, 6 p, 7 p, and 4f were observed in above threshold ionization (ATI) at laser intensities of 2 × 10 13 W cm −2 and 1 × 10 13 W cm −2 . The PADs from the 5 p ( 4f ) state for zero, first, second and third order ATI peaks were measured. We observed that for the two selected laser intensities the angular distribution of photoelectrons showed only slight variations. The PADs exhibit main lobes within ∼60° degrees from the laser polarization and additional lobes that become more pronounced with the increasing ATI peak number. Besides a general analytical representation of the observed angular dependences, the experimental PADs for each ATI peak were fitted with Legendre polynomials accounting for different ionization channels. The good agreement between the experimental data and fitting functions allowed to evaluate the contributions of the ionization channels to the observed ATI orders. The calculations of the photoelectron spectra by numerically solving the time-dependent Schrödinger equation in a single active electron approximation produced agreement with the experiment in the main features of the spectra, while differences in more subtle details were observed.